A history of Zoroastrianism - Boyce, Mary. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1989)
This volume traces the history of Zoroastrianism at times and places where its existence has previously been largely ignored, or treated only episodically. Literary, archaeological and numismatic evidence has been drawn on (some of it only recently brought to light), and local developments are distinguished. In Iran itself some 200 years of Macedonian rule had little effect on the national religion. To the east, Zoroastrianism survived in the Greco-Bactrian kingdoms and under Mauryan suzereinty, where it came into contact with Buddhism. In Eastern Mediterranean lands it was maintained by Iranian expatriates well down into Roman imperial times. They adopted Greek for their written tongue, and Zoroastrian doctrines thus became known in the Greco-Roman world. Study is made accordingly of Zoroastrian contributions to Hellenistic thought, and to Judaism, Christianity and Mithraism; and an excursus provides a thorough reassessment of the Zoroastrian pseudepigrapha.